Active methodologies in the university science communication course during the Covid-19 pandemic - Viana, Wesley Roberth Lima; Chagas, Jéssica da Cruz; Ferreira, Rosilene Gomes da Silva; Battaini, Vivian (JRG Journal of Academic Studies, 2024)
This work aimed to analyze the active methodologies used in the extension course: “Education and Scientific Dissemination in the midst of the Pandemic”. The work methodology was based on the case study and used participant observation and document analysis as data collection techniques. The first occurred in course planning and evaluation meetings, during meetings. The second focused on conversations via WhatsApp and Google Classroom, regarding the teaching materials produced and the evaluation of the course participants. Data analysis was based on data triangulation. The results included the valorization of students' prior knowledge and the joint construction of knowledge, the intensification of the use of digital technologies, the co-production of materials, in addition to joint and flexible planning to improve scientific dissemination. The training was fundamental to strengthening scientific education, highlighting the promotion of dialogue and the joint creation of dissemination materials.